Role of the granzyme family in rheumatoid arthritis: Current Insights and future perspectives - Zheng, Yixin; Zhao, Jianan; Shan, Yu; Guo, Shicheng; Schrodi, Steven J.; He, Dongyi (Frontiers in Immunology, 2023)
Rheumatoid arthritis (RA) is a complex autoimmune disease characterized by chronic inflammation that affects synovial tissues of multiple joints. In recent years, researchers have identified a link between the granzyme family of enzymes secreted by cytotoxic lymphocytes (cytotoxic T cells and natural killer cells) and the pathogenesis of RA. Granzymes (Gzms) are serine proteases that are released into the immune synapse between cytotoxic lymphocytes and target cells. They enter target cells with the help of perforin to induce programmed cell death in inflammatory and tumor cells. Gzms also have extracellular functions in promoting inflammation and degrading the extracellular matrix in patients with autoimmune and infectious diseases. Previous evidence has suggested that Gzms may play a role in the development and progression of RA. Increased levels of Gzms have been found in the serum (GzmB), plasma (GzmA, GzmB), synovial fluid (GzmB, GzmM), and synovial tissue (GzmK) of patients with RA. Moreover, Gzms may contribute to inflammation by degrading the extracellular matrix and promoting cytokine release. They are thought to be involved in RA pathogenesis and have the potential to be used as biomarkers for RA diagnosis, although their exact role is yet to be fully elucidated. The purpose of this review was to summarize the current knowledge regarding the possible role of the granzyme family in RA, with the aim of providing a reference for future research on the mechanisms of RA and the development of new therapies.